Meningkatkan Minat Baca Siswa SDIT AT-Tibtan Melalui Program Library Visit - Nurhikmah (Alpatih Harapan Semesta, 2024)
Reading interest is one of the key factors in developing students' literacy skills from an early age. This article discusses the importance of the library visit programme in increasing elementary school students' interest in reading. This type of research uses descriptive qualitative research, with a fenamology approach. In addition, the data analysis technique used is data triangulation. This article identifies the introduction of the library visit programme, its implementation, efforts to improve students' reading skills, and students' activities during library visits. The creative activities conducted during the library visit proved to be able to increase learners' engagement and motivate them to read more. In addition, learners get a new atmosphere. The results showed that the library visit programme had a positive impact on increasing students' interest in reading and literacy skills. Collaboration between schools, libraries, teachers and parents was seen as a key factor in the success of the programme. With the right support, the library visit programme can be an effective tool in promoting literacy education among primary school students. The library visit programme has great potential to increase elementary students' interest in reading and contribute to improving the quality of education in Indonesia.